BASALTIC BRECCIAS IN THE UPPER OCEANIC CRUST, HOLE 504B (COSTA RICA RIFT, PACIFIC OCEAN) - Tartarotti, Paola; Aligi Pasquaré, Federico (Ofioliti, 2003)
DSDP/ODP Hole 504B is located in the Panama Basin, eastern Pacific ocean, 200 km south of the Costa Rica Rift, which is a 171-km-long east-west trending segment of the Cocos-Nazca Spreading Center. Hole 504B penetrates 2.1 km into 5.9 m.y. old oceanic crust consisting, from the top to the bottom, of pillow lavas (571.5 m) covered by 274.5 m of sediments; a transition zone (209 m), and a lower zone composed of diabasic dikes (1056 m). Basaltic breccia is a significant component of the volcanic section, down to the upper part of the sheeted dike complex. Six main types of breccias were recognized through core and petrographic observations. Only jigsaw-puzzle breccias can be interpreted as tectonic. Although overall pore-fluid pressures slightly lower than hydrostatic were measured at Hole 504B, jigsaw-puzzle breccias may have formed under local conditions of suprahydrostatic fluid pressure, mostly beneath impermeable barriers such as massive basaltic flows. High fluid pressure conditions were favoured by a structural setting allowing the action of a fault-valve. Highly fractured zones identified by core observations and geophysical logs at depths of about 400-550 mbsf and 800-1100 mbsf, respectively, likely correspond to faults, creating the conditions for a fault-valve mechanism. Breccias of the stockwork zone were produced by focused fluid flow associated with a discharge hydrothermal cycle. All the other breccias recognized in the studied section are interpreted as deriving from either in situ fragmentation of basalts or sedimentation of basaltic debris.